Preschool Mathematics Intervention Can Significantly Improve Student Learning Trajectories Through Elementary School - Denis Dumas; Daniel McNeish; Julie Sarama; Douglas Clements (SAGE Publishing, 2019)
Perhaps more than at any other time in history, the development of mathematical skill is critical for the long-term success of students. Unfortunately, on average, U.S. students lag behind their peers in other developed countries on mathematics outcomes, and within the United States, an entrenched mathematics achievement gap exists between students from more highly resourced and socially dominant groups, and minority students. To begin to remedy this situation, educational researchers have created instructional interventions designed to support the mathematical learning of young students, some of which have demonstrated efficacy at improving student mathematical skills in preschool, as compared with a business-as-usual control group. However, the degree to which these effects last or fade out in elementary school has been the subject of substantial research and debate, and differences in scholarly viewpoints have prevented researchers from making clear and consistent policy recommendations to educational decision makers and stakeholders. In this article, we use a relatively novel statistical framework, Dynamic Measurement Modeling, that takes both intra- and interindividual student differences across time into account, to demonstrate that while students who receive a short-term intervention in preschool may not differ from a control group in terms of their long-term mathematics outcomes at the end of elementary school, they do exhibit significantly steeper growth curves as they approach their eventual skill level. In addition, this significant improvement of learning rate in elementary school benefited minority (i.e., Black or Latinx) students most, highlighting the critical societal need for research-based mathematics curricula in preschool.